Structural and Mechanical Strength of Proton Radiation Processed Polyethylene Terephthalate - Sahoo, M.; Mallick, B.; Rout, S.; Dash, G. N. (Journal of Scientific Research, 2020)
The change in structural and mechanical behavior of polyethylene terephthalate (PET) due to 2.4 MeV proton has been studied. Radiation processing of PET polymer is carried out using different low doses such as 0.2, 2.0, and 20 kGy. The Physics of microstrain and radiation-induced mesophase formation are analysed. X-ray investigation indicates that proton-induced structural modification takes place in the material. Apart from usual diffraction peaks, a low intensity broad peak is observed at small angle of about 2q =10º, when the fibre axis is mounted parallel to the X-ray direction. Such peak is absent in the diffraction spectrum when the fibre axis is mounted perpendicular to the beam direction. The appearance of the extra peak in a particular orientation confirms that, the phase is 2-dimensionally oriented (mesophase). The Young’s modulus (Y) of this irradiated PET sample is found to be more than that of the virgin sample with the highest value recorded for a dose of 2.0 kGy. The decrease in Y for higher dose (20 kGy) may be due to enhanced ion-induced microstrain in the sample, causing degradation in mechanical strength.